Advancing Social Capital through Participatory Approaches: Case of Community-Based Slum Upgrading in Yogyakarta, Indonesia - Muhammad Nelza Mulki Iqbal (EMARA: Indonesian Journal of Architecture, 2018)
Social capital discourse has come to be the foremost and essential aspects in achieving sustainable development, participatory democracy and just cities. Indonesia is like most Asian countries where people spatially and socially co-live in a community that is related to a network of small clusters. However, the formal study related to social capital is hardly founded. Based on its characters, Gotong Royong which is a socio-cultural ethic of the togetherness philosophy in Indonesia can be perceived as an Indonesian social capital practice. Advancing social capital through participatory approaches will need a deep consideration about the role of professional and community engagement. Successful collaborations between wider actors in participatory approaches could lead to a fundamental transformation that can both preserve and nurture social capital values. High level of social capital within communities can potentially underpin the successful community participation towards communal goals.